Gamma Knife(™) Radiosurgery Treatment Planning for Small Animals using High-Resolution 7T Micro-magnetic Resonance Imaging - Wiant, D. (2009)
Gamma Knife(™) stereotactic radiosurgery is capable of providing small, high gradient dose distributions to a target with a high level of precision, which makes it an excellent choice for studies of focal irradiations with small animals. However, the Gamma Knife stereotactic radiosurgery process makes use of a human-sized fiducial marker system that requires a field of view of at least 200 mm(2) to relate computed tomography and magnetic resonance images to the Gamma Knife treatment planning software. Thus the Gamma Knife fiducial marker system is five to six times larger than a typical small animal subject. The required large field of view limits the spatial resolution and structural detail available in the animal treatment planning image set. In response to this challenge we have developed a custom-designed stereotactic jig and miniature fiducial marking system that allow small bore high-resolution micro-imaging techniques, such as 7T MR and micro-CT, to be used for treatment planning of Gamma Knife stereotactic radiosurgery focal irradiation of small animals.